2019
DOI: 10.3390/pathogens8010040
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans at Host Barrier Sites: Pattern Recognition Receptors and Beyond

Abstract: Over the last decades, fungal infections have emerged as a growing threat to human health. Although the human body is at potential risk, various body sites host several commensal fungal species, including Candida albicans. In healthy individuals, C. albicans colonizes different mucosal surfaces without causing harm, while under diverse circumstances the fungus can proliferate and cause disease. In this context, the understanding of host–C. albicans interactions in health and during infection may lead to novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 145 publications
1
51
0
1
Order By: Relevance
“…Such an event has also been associated with a milder host response, compared to the response followed by a normal opsonization process, enabling intracellular survival and avoiding the hostile extracellular niche (Würzner and Zipfel, 2004). To date, it is still unclear whether C. albicans uses a Trojan horse-like mechanism for host cell invasion, let alone if such an event would take place with the help of host complement receptors (Swidergall, 2019). Molecular mimicry of host complement proteins is another potential route of host response evasion.…”
Section: Recruitment Of Complement Regulators On the Cell Surfacementioning
confidence: 99%
“…Such an event has also been associated with a milder host response, compared to the response followed by a normal opsonization process, enabling intracellular survival and avoiding the hostile extracellular niche (Würzner and Zipfel, 2004). To date, it is still unclear whether C. albicans uses a Trojan horse-like mechanism for host cell invasion, let alone if such an event would take place with the help of host complement receptors (Swidergall, 2019). Molecular mimicry of host complement proteins is another potential route of host response evasion.…”
Section: Recruitment Of Complement Regulators On the Cell Surfacementioning
confidence: 99%
“…Notably, recent studies have shown that intraspecific differences not associated with fungal morphology between C. albicans isolates lead to diverse recognition/immune responses by the oral epithelium (Kirchner et al, 2019), although virtually all strains induce conserved IL-17-mediated responses (Schönherr et al, 2017). Thus, this highlights the importance of other fungal factors that contribute to the balance between commensalism and pathogenesis in the oral cavity (Swidergall, 2019).…”
Section: Candida Albicans As An Essential Part Of the Healthy Mycobiotamentioning
confidence: 99%
“…Mucosal immunity to Candida has extensively been reviewed recently, including its recognition by and interactions with epithelial cells (Naglik et al, 2017;Richardson et al, 2018;Nikou et al, 2019;Swidergall, 2019), and the role of innate immune cells FIGURE 1 | Mucosal innate immunity to Candida albicans. Recognition of C. albicans by epithelial cells is mainly mediated by the β-glucan receptor Eph2A.…”
Section: Anti-candida Innate Immunity At the Mucosamentioning
confidence: 99%
See 2 more Smart Citations